Synergizing Soil Restoration and Circular Economy: Integrated Application of Nano-particle Enhanced Compost (NEC) and Husk Charcoal - Suyani, Ida Sugeng; Nurhidayati, Nurhidayati; Hartanti, Aprilia; Oktaviani, Dewi Anggun; Susyanti, Jeni; Tito, Sama’ Iradat; Rahmansyah, Ahmad Iskandar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2026)
The progressive decline in rice productivity, currently reaching 7–8 tons/ha in Klaseman Village, is primarily attributed to soil fertility degradation resulting from the intensive and long-term application of inorganic chemical fertilizers. This environmental challenge necessitates a strategic technology transfer to remediate soil health and enhance farmer self-sufficiency through sustainable practices. This community service initiative aimed to elevate the technical proficiency and managerial capacity of the